God in the Perspective of Mawlana Abu Al-Kalam Azad - Pratama, Aunillah Reza; Arminsa, Muhammad Lytto Syahrum (Universitas Islam Negeri Raden Intan Lampung, 2023)
Abstract;The article explores Mawlana Abu Al-Kalam Azad's viewpoint that God cannot be understood using human reason. This study is categorized as library research. The study's findings suggest that the essence of all religions is fundamentally obedience to God and the need to do good. With God's and religion's unity, it is necessary for all human beings, regardless of religion, to appreciate and treat one another kindly.Keywords:God; Mawlana Abu Al-Kalam Azad. Abstrak;Tulisan ini mengkaji tentang pandangan Mawlana Abu Al-Kalam Azad tentang Tuhan, dimana menurutnya Tuhan tidak pernah dicapai oleh akal manusia. Penelitian ini tergolong dalam penelitian pustaka (Library Research). Hasil penelitian menybutkan bahwa esensi semua agama pada dasarnya adalah penghambaan kepada Tuhan dan keharusan berbuat baik. Dengan kesatuan Tuhan dan kesatuan agama tersebut, ada keharusan bagi seluruh umat manusia, apa pun agamanya untuk saling menghormati dan saling berbuat baik satu sama lain.Kata Kunci: Tuhan; Mawlana Abu Al-Kalam Azad.